ANALISIS PENGARUH KEHALUSAN ABU TERBANG (ABU SEKAM PADI) TERHADAP DURABILITAS DAN FLEKSIIBILITAS AC-BC NR - Rosyad, Farlin; Febriansyah, Febriansyah (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
Construction progress, whether for buildings or roads, can be used to determine how well an area is performing. The development of an effective transportation system can facilitate the entry and exit of raw materials or finished goods to other areas, improving the economy of local communities as a whole. The method used in this research is by adding a percentage of rice husk ash of 0% (as a comparison), 4%, 6% and 8% as a substitute material for the fine fraction in the AC-BC nr asphalt mixture. To determine the effect of the fineness of rice husk ash on the durability and flexibility of AC-BC (Asphalt Concrete – Binder Course) nr. To find out what the optimum level of variation of rice husk ash mixture is as a substitute material for AC-BC (Asphalt Concrete - Binder Course) asphalt mixture nr.. The optimum residual flow value in the 2-4% zone is 3.9 mm, while the lowest residual flow value decreased in the 3-8% zone with a value of 3.07 mm. Flow values that are below the minimum limit cause cracking and low durability. The highest residual marshall value is in the 2-4% zone with a value of 96.68%, while the lowest residual marshall value is in the normal range with a value of 91.69%. The minimum requirement for residual marshall is 90%.Keywords: Rice husk ash, Asphalt sir-20, Flow, Residual Marshall, Durability, Flexibility.